2022
DOI: 10.1161/circheartfailure.121.008726
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular and Right Atrial Function Are Less Compromised in Pulmonary Hypertension Secondary to Heart Failure With Preserved Ejection Fraction: A Comparison With Pulmonary Arterial Hypertension With Similar Pressure Overload

Abstract: Background: Heart failure with preserved ejection fraction (HFpEF) is a prevalent disorder for which no effective treatment yet exists. Pulmonary hypertension (PH) and right atrial (RA) and ventricular (RV) dysfunction are frequently observed. The question remains whether the PH with the associated RV/RA dysfunction in HFpEF are markers of disease severity. Methods: To obtain insight in the relative importance of pressure-overload and left-to-right inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The change in the Fulton Index of STING −/− mice, specifically, has significant translational potential, as patients with even mild preservation of right heart function have been shown to perform significantly better with slower disease progression. 66,67 Future studies regarding STING should thus focus on the specific mechanism preventing right-heart in end-stage PH patients, in light of our findings and other studies demonstrating that STING −/− mice were protected from cardiovascular diseases. 68,69 In addition, we demonstrated that MDSCs recruited to the lungs of STING −/− mice exposed to chronic hypoxia exhibit a decrease in expression of immune checkpoint PD-L1.…”
Section: Discussionmentioning
confidence: 72%
“…The change in the Fulton Index of STING −/− mice, specifically, has significant translational potential, as patients with even mild preservation of right heart function have been shown to perform significantly better with slower disease progression. 66,67 Future studies regarding STING should thus focus on the specific mechanism preventing right-heart in end-stage PH patients, in light of our findings and other studies demonstrating that STING −/− mice were protected from cardiovascular diseases. 68,69 In addition, we demonstrated that MDSCs recruited to the lungs of STING −/− mice exposed to chronic hypoxia exhibit a decrease in expression of immune checkpoint PD-L1.…”
Section: Discussionmentioning
confidence: 72%
“…Some of them also develop a pre‐capillary component, leading to a combined pre‐ and post‐capillary PH 285,286 . RV dysfunction and PH are confirmed as major determinants of the poor prognosis of HF patients, including those with HFpEF 287–291 . In HFpEF and PH, diffuse RV fibrosis was described 292 …”
Section: Comorbiditiesmentioning
confidence: 99%
“…Thus, non‐invasive measurement of RA parameters for PH risk stratification 34 somewhat embodies assessment of RV diastolic function, as suggested by the authors 100 . However, RA impairment and RA pressure increase may not always be the consequence of RV dysfunction per se and must be evaluated in the context of the underlying disease, as recently shown by van Wezenbeek et al ., comparing PAH and PH in HFpEF at matched levels of pressure overload 101 . Consequently, simple non‐invasive surrogates of RV diastolic function are sought and may attract attention in the near future.…”
Section: Discussionmentioning
confidence: 99%